2020
DOI: 10.26444/aaem/118130
|View full text |Cite
|
Sign up to set email alerts
|

Environmental soil contamination by <i>Toxocara</i> species eggs in public places of Ilam, Iran

Abstract: Introduction. The purpose of the study is to assess environmental contamination by Toxocara species eggs in public places in the city of Ilam, Ilam Province, southwest Iran Materials and method. Between September 2018 and March 2019, 130 soil samples were collected from public places of 5 district municipalities of Ilam, southwest Iran. Soil samples were examined by microscopy following flotation method by sodium nitrate. Results. Soil analysis showed that 5.88% of the soils stored, 52.54% from gardens, 29.42%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…This result was slightly different from a previous report where contamination was detected in 12.0% of the soil samples collected from schools in Sakon Nakhon Province [6] in the northeastern region and in 18.3% of the soil samples in Nakhon Si Thammarat Province [7] in the southern region. Our results revealed higher contamination rates than those in Iran (13.0%) [18], Sri Lanka (12.0%) [19], Poland (1.6%) [20], and Brazil (0.5%-8.3%) [12,21], but lower than those reported in Iran (18.0%-47.5%) [9,22,23], Malaysia (24%) [2], Poland (20.7%) [17], Russia (23.3%) [24], Brazil (27.3%-38.4%) [25,26], Greece (17.1%) [27], Peninsula (26.6%) [28], Portugal (63.2%) [29], Serbia (22.0%-26.0%) [30], Turkey (19.4%) [31], and Germany (23.2%) [32]. Toxocara spp.…”
Section: Discussioncontrasting
confidence: 70%
“…This result was slightly different from a previous report where contamination was detected in 12.0% of the soil samples collected from schools in Sakon Nakhon Province [6] in the northeastern region and in 18.3% of the soil samples in Nakhon Si Thammarat Province [7] in the southern region. Our results revealed higher contamination rates than those in Iran (13.0%) [18], Sri Lanka (12.0%) [19], Poland (1.6%) [20], and Brazil (0.5%-8.3%) [12,21], but lower than those reported in Iran (18.0%-47.5%) [9,22,23], Malaysia (24%) [2], Poland (20.7%) [17], Russia (23.3%) [24], Brazil (27.3%-38.4%) [25,26], Greece (17.1%) [27], Peninsula (26.6%) [28], Portugal (63.2%) [29], Serbia (22.0%-26.0%) [30], Turkey (19.4%) [31], and Germany (23.2%) [32]. Toxocara spp.…”
Section: Discussioncontrasting
confidence: 70%
“…Accordingly, subdivisions and sampling patterns vary between studies. While some investigators use grid-based subdivisions with sampling every single ( Bojanich et al, 2015 ) to fourth or fifth square meter ( Raissi et al, 2020 ), other researchers´ subdivisions are numbered with sampling spots being randomly selected by numeration or lot ( Fig. 2 f) ( Carabin et al, 1998 ).…”
Section: Sampling and Isolation Of Ascarid Ova From Environmental Mediamentioning
confidence: 99%
“…On the one hand, sample size is dependent on the dimensions of the study area: the bigger the area, the more samples should be taken. Many of the above-mentioned strategies avoid this problem by sampling in defined intervals such as square meters ( Bojanich et al, 2015 ; Raissi et al, 2020 ). On the other hand, contamination heterogeneity critically influences the sample size.…”
Section: Sampling and Isolation Of Ascarid Ova From Environmental Mediamentioning
confidence: 99%
“…Dogs are the canids that thoroughly have adapted to human habitation, and they improve the physical, mental, and social health of their owners, particularly children [9]. On the other hand, domestic dogs and cats are the key reservoirs of the infection, and they have a major part in the epidemiology of human toxocariasis, as they frequently excrete into human environment [10][11][12]. The global estimations revealed that the prevalence of Toxocara in dogs was 11.1% with ≥100 million dogs infected with this parasite globally [12].…”
Section: Introductionmentioning
confidence: 99%